Effectiveness of interpretation products at Tioman Marine Park information centre - Heng, Hui Shan (2016)
People care about things they know, appreciate, and understand. Things that people care about are perpetuated; things they do not care about are forgotten. Interpretation is a keystone in helping people to appreciate, understand, and care about the environment. This study focuses on evaluation of the interpretation products applied in the Tioman Marine Park Information Centre that will provide information to help develop a high level of awareness among the tourists and the host communities. It is important to understand the interest between visitors and exhibits that being displayed in this information centre in term of giving information and awareness about the marine ecosystem. Interpretive objectives, Tilden’s principles and interpretive signs were used as key indicators in the assessment of the interpretative effectiveness of the Tioman Marine Park Information Centre. The exhibits were measured according to in order to evaluate the criteria of an interpretive exhibit. The results had shown that some exhibits meet the prescribed elements of interpretation while some do not. It is hoped that this finding will strive the Tioman Marine Park Information Centre to create unique and meaningful interpretative exhibits with the ability to effectively fulfill their educational missions to public.